Archaeology of the Pleistocene-Holocene transition in Portugal : Synthesis and prospects - Gameiro, Cristina (2020)
The Tardiglacial of Portugal has been associated with the Magdalenian culture and lithic industries characterized by tool miniaturization, a diversity of microlith types, and the absence of a intentional blade production. The technological characterization, the chronology and the phasing of the Portuguese Magdalenian have been defined based on data recovered from open-air sites of the Estremadura region (Central Portugal). This paper presents an overview of the research undertaken over the last twenty-five years, including results from research and preventive archaeology fieldwork outside this region, namely in the Côa, Sabor and Vouga Valleys (northern Portugal), as well as in the Guadiana Valley and Algarve regions (southern Portugal). Our chronological boundaries are the Greenland Stadial 2-1b and the 8.2 ka event, from Early Magdalenian to Early Mesolithic. Regarding vegetation, deciduous Quercus underwent expansion during the warm phases of the Tardiglacial and retracted during cold ones, when pines increased. After the Solutrean, the faunal assemblages show a decrease in the variability of the represented species and an increase in fish, birds, small mammals and rabbits (Oryctolagus cuniculus). Concerning the cultural sequence, the Middle Magdalenian remains uncharacterised. After the Upper Magdalenian, and thenceforward, the use of local raw materials and of cores-on-flakes (burin or carinated endscraper type) for bladelet production gradually increased. In terms of lithic armatures typology, a four-stage sequence can be discerned: 1) Upper Magdalenian with axial points rather than backed bladelets, quite common in previous phases; 2) Final Magdalenian with an increase in the diversity of armature types; 3) Azilian with geometric microliths, curved backed points (Azilian points) and Malaurie points, and 4) Early Mesolithic without retouched bladelet tools or at best a persistence of Azilian armature types. There were some changes in the Palaeolithic rock art of the Douro basin between phase 3 (Final Magdalenian) and phase 4 (Late Azilian): figurative animal representations give place to animal depictions characterized by their geometrical bodies, often filled-in, and red deer becomes the best-represented animal.